Ammonia Oxidation by the Arctic Terrestrial Thaumarchaeote Candidatus Nitrosocosmicus arcticus Is Stimulated by Increasing Temperatures - Alves, Ricardo J. Eloy; Kerou, Melina; Zappe, Anna; Bittner, Romana; Abby, Sophie S.; Schmidt, Heiko A.; Pfeifer, Kevin; Schleper, Christa (Frontiers in Microbiology, 2019)
Climate change is causing arctic regions to warm disproportionally faster than those at lower latitudes, leading to alterations in carbon and nitrogen cycling, and potentially higher greenhouse gas emissions. It is thus increasingly important to better characterize the microorganisms driving arctic biogeochemical processes and their potential responses to changing conditions. Here, we describe a novel thaumarchaeon enriched from an arctic soil, Candidatus Nitrosocosmicus arcticus strain Kfb, which has been maintained for seven years in stable laboratory cultures as an aerobic ammonia oxidizer with ammonium or urea as substrates. Genomic analyses show that this organism harbors all genes involved in ammonia oxidation and in carbon fixation via the 3-hydroxypropionate/4-hydroxybutyrate cycle, characteristic of all AOA, as well as those for urea utilization and potentially also for heterotrophic metabolism, similar to other AOA. Although Ca. N. arcticus oxidizes ammonia optimally at 20 to 28°C, it showed growth at faster rates at 4 °C without detectable nitrite production. Growth independent of ammonia oxidation was observed at lower temperatures in multiple cultures from different inocula and at different enrichment stages, based on amoA and 16S rRNA gene quantification, but could not be induced systematically in the laboratory. These results add to cumulating evidence for a greater metabolic and physiological versatility of AOA and suggest that increasing temperatures might drastically affect archaeal function in arctic soils, potentially by stimulating nitrification activity of archaeal populations that thrive on alternative metabolism(s) under colder conditions.